2015
DOI: 10.1088/0953-8984/27/31/313201
|View full text |Cite
|
Sign up to set email alerts
|

Strain engineering in semiconducting two-dimensional crystals

Abstract: One of the fascinating properties of the new families of two-dimensional crystals is their high stretchability and the possibility to use external strain to manipulate, in a controlled manner, their optical and electronic properties. Strain engineering, understood as the field that study how the physical properties of materials can be tuned by controlling the elastic strain fields applied to it, has a perfect platform for its implementation in the atomically thin semiconducting materials. The object of this re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
439
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 457 publications
(458 citation statements)
references
References 173 publications
(370 reference statements)
13
439
2
4
Order By: Relevance
“…This reversible modulation of the band gap could be used to make wavelength tunable phototransistors 16 , or MoS 2 strain sensors that have a sensitivity comparable to their state of the art silicon counterparts 20 . Moreover it has been suggested that strain could also improve the performance of MoS 2 transistors 21 , or could be used to create broadband light absorbers for energy harvesting 22 .The effect of strain on the band gap of 2D TMD's has been reported in a number of studies [9][10][11][12]20,23,24 , including uniaxial strains of up to ~4 % 25 and biaxial strains of up to ~3 % produced in highly localized sub-micron areas 26 . Band gap shifts in MoS 2 of ~300 meV have been induced by using very large hydrostatic pressures 27 , and tensile strain has induced shifts of as much as ~100 meV 11 .…”
mentioning
confidence: 99%
“…This reversible modulation of the band gap could be used to make wavelength tunable phototransistors 16 , or MoS 2 strain sensors that have a sensitivity comparable to their state of the art silicon counterparts 20 . Moreover it has been suggested that strain could also improve the performance of MoS 2 transistors 21 , or could be used to create broadband light absorbers for energy harvesting 22 .The effect of strain on the band gap of 2D TMD's has been reported in a number of studies [9][10][11][12]20,23,24 , including uniaxial strains of up to ~4 % 25 and biaxial strains of up to ~3 % produced in highly localized sub-micron areas 26 . Band gap shifts in MoS 2 of ~300 meV have been induced by using very large hydrostatic pressures 27 , and tensile strain has induced shifts of as much as ~100 meV 11 .…”
mentioning
confidence: 99%
“…the modification of a material's optical/electrical properties by means of mechanical stress. 16 This is in contrast to conventional 3D semiconductors that tend to break for moderate deformations. Very recent theoretical works explore the effect of strain on the band structure and optical properties of black phosphorus, predicting an even stronger response than in other 2D semiconductors such as transition metal dichalcogenides.…”
Section: Textmentioning
confidence: 89%
“…As a consequence, the electronic and optical properties of this material can be efficiently tuned by applying an external bias voltage [16][17][18][19][20] or by strain engineering. [21][22][23][24][25] In particular, it is possible to drive a semiconductor to semimetal transition, with the appearance of Dirac like dispersion. [16][17][18]26 In this paper we study the electronic spectrum of biased BP in the presence of a strong magnetic field.…”
Section: Introductionmentioning
confidence: 99%